Comparative Flexural Behavior of Precast Beam Joint Loop and Loop-Pin Models under Static Loads - Padang, Israel; Djamaluddin, Rudy; Parung, Herman (Engineering, Technology & Applied Science Research, 2026)
This study investigates the flexural behavior of Precast Beams with two connection models—Loop (PB-L) and Loop-Pin (PB-LP)—compared to a Monolithic Beam (MB) as the control. Experimental flexural tests were conducted using a two-point static loading setup. The key parameters analyzed include initial flexural capacity (Pcr, Mcr), yield capacity (Py, My), ultimate capacity (Pu, Mult), deflection (∆cr, ∆y, ∆ult), as well as steel and concrete strain behavior. The PB-LP beam exhibited the highest initial stiffness and cracking load capacity (Pcr = 9.42 kN; Mcr = 6.66 kNm), approximately 65% higher than MB, but showed lower steel and concrete yield strain compared to PB-L and MB. Conversely, PB-L closely matched the MB in terms of yield and ultimate capacities. All beam specimens achieved ductility ratios between 7 and 7.4, which classified them as high-ductility elements, indicating adequate plastic deformation capacity for seismic applications. These findings demonstrate that both loop and loop-pin connections are viable for precast systems in low-cost housing in seismic regions, with PB-L providing monolithic-like behavior and PB-LP excelling in initial crack resistance.